VIDEO ASSIGNMENT AS PROJECT-BASED LEARNING IMPLEMENTATION: STUDENTS' EXPERIENCES (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
This study aims to describe students' experiences with video-based assignments. The researchers were interested in determining how and what students thought about the video-format assignment that was assigned to them.  Specifically, the objectives of this study are: 1) to categorize the types of video assignments that are commonly assigned to students by lecturers; 2) to examine the perspectives of students about the types of video assignments; and 3) to identify the primary challenges and difficulties that students frequently encounter during the production process of these video assignments. To achieve this objective, the researchers employed two data collection techniques: online surveys and interviews. More than 100 students completed the online survey using a Google Form. Subsequently, the researchers proceeded to conduct interviews with a selection of respondents derived from the summary of questionnaire respondents. The findings of this study indicated that the video assignments are mostly an individual work. Students do not perceive this type of activity as burdensome, provided that not all courses require assignments in the same format, specifically video format. The authors further elucidated that the primary challenges encountered in the production of video assignments pertain to the preparation of materials and the subsequent editing process. In short, these findings are expected to serve as the predominant determinant for implementing video assignments among students in the foreseeable future, enabling them to successfully and optimally complete such projects.
Keywords: Students’ Experience; Project-Based Learning; Video-Formatted Assignment